Knowledge, awareness, perceptions, and practices on solid waste management of households in selected urban barangays in Sorsogon City, Sorsogon, Philippines - Jeremias, Hazel Ivy M.; Fellizar, Francis Mark Dioscoro (2019)
The study examined the relationship of socio-demographic characteristics and environmental knowl- edge, awareness, and perception with the solid waste management (SWM) practices of respondent households in Sorsogon City, Sorsogon, Philippines. Two-stage sampling was conducted to select sample households from 10 urban barangays in Sorsogon City. Ninety-five respondents were sur- veyed using a survey questionnaire and 11 key informants were interviewed using key informant interview guides. Survey results revealed that 69% of households had average levels of knowledge while 54% were aware of the local waste management situation and the local and national policies on SWM. Survey respondents, however, also exhibited a “not-in-my-backyard” (NIMBY) attitude and perceived that material recovery facilities and waste collection points should be located far from their homes. Eighty-two percent of survey respondents engaged in segregation while 85% engaged in selling recyclables, citing cleanliness and additional income as motivators. Burning dried leaves and household wastes and dumping garbage in rivers are still practiced. Findings showed weak relationships between SWM practices of households and respondent’s age, educational attainment, household size, total household monthly income, and level of environmental knowledge, awareness, and perception. The study revealed, however, that age and household size have a strong correlation with SWM practices. Results also showed that educational attainment and SWM practices have a moderate correlation, while no relationship was found between total monthly household income and SWM practices. Moreover, the study found that the levels of environmental knowledge, awareness, and perception of households do not translate into SWM practices, implying the need to strengthen information, education, and communication campaigns.
Keywords: Solid waste management